Determination of the stereochemistry of anhydroerythromycin A, the principal degradation product of the antibiotic erythromycin A - Hassanzadeh, A; Helliwell, M; Barber, J (Organic & biomolecular chemistry, 2006)
Anhydroerythromycin A arises from the acid-catalysed degradation of erythromycin A both in vitro and in vivo. It has negligible antibacterial activity, but inhibits drug oxidation in the liver, and is responsible for unwanted drug-drug interactions. Its structure has 18 chiral centres common with erythromycin A, but C-9 (the spiro carbon) is also chiral in anhydroerythromycin and its stereochemistry has not previously been reported; both 9R- and 9S-anhydroerythromycin A are plausible structures. An understanding of the chirality at C-9 was expected to throw light on the mechanism of acid-catalysed degradation of erythromycin A, a subject that has been debated in the literature over several decades. We now report a determination of the three-dimensional structure of anhydroerythromycin A, including the stereochemistry at C-9, by NMR and molecular modelling. In parallel, the relative stereochemistry of anhydroerythromycin A 2'-acetate was determined by X-ray crystallography. Both compounds were shown to have 9R stereochemistry, and anhydroerythromycin A exhibited considerable conformational flexibility in solution.